Reducing False Negative PCR Test for COVID-19 - Fatemeh Bahreini, PhD; Rezvan Najafi, PhD; Razieh Amini, PhD; Salman Khazaei, PhD; Saeid Bashirian, PhD (Global Health and Education Projects, Inc., 2020)
As the SARS-CoV-2 (COVID-19) pandemic spreads rapidly, there is need for a diagnostic test with high accuracy to detect infected individuals especially those without symptoms. Real-time polymerase chain reaction (RT-PCR) is a common molecular test for diagnosing SARS-CoV-2. If some factors are not taken into consideration when performing this test, it can have a relatively large number of false negative results. In this article, we discuss important considerations that could lead to false negative test reduction. Key words: • SARS-CoV-2 • COVID-19 • Real time polymerase chain reaction • RT-PCR test • Diagnosis • False negatives • Genetics • Emerging disease   Copyright © 2020 Bahreini et al. Published by Global Health and Education Projects, Inc. This is an open-access article distributed under the terms of the Creative Commons Attribution License (CC BY 4.0)which permits unrestricted use, distribution, and reproduction in any medium, provided the original work, first published in this journal, is properly cited.